Nutritional Practices among Expectant Mothers in Jos North Local Government Area of Plateau State, Nigeria - Haruna, Elizabeth A. (NIU Journal of Humanities; Vol 5 No 3 (2020): KIU Journal of Humanities, Vol. 5 No. 3, September 2020, 2020)
he study was carried out to help find out the nutritional knowledge and practices among expectant mothers in Jos North Local Government Area of Plateau State. The survey research design was used for the study. The population of the study is made up of all expectant mothers in Jos North Local Government Area of Plateau State, out of these the total sample size of 225 were used for the study, a structured questionnaire of six sections was used to elicit information on the nutritional practices among expectant mothers, health problems associated with the nutritional practices of expectant mothers, foods commonly eaten by expectant mothers, cultural practices of expectant mothers, health problems of cultural practices associated with nutrition of the expectant mothers. The instrument was given to three experts in research, who of whom are from the department of Physical and Health Education and one from test and measurement department of the Faculty of Education University of Jos whose input on the instrument were very helpful. It was pretested using respondent with similar characteristics to those in the area of the main study and a reliability coefficient index of 0.8 was obtained, which was seen as a reliable figure for the instrument to be used for the present study. The public health educators and workers should organize seminars on nutritional knowledge and practices among expectant mothers in the area of study. Expectant mothers should eat more during pregnancy to avoid fatal malnutrition, as well as eat balanced diet during the period of pregnancy Keywords: Nutritional practices, expectant mothers, Jos  North